1999
DOI: 10.1121/1.427109
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric functions for gap detection in noise measured from young and aged subjects

Abstract: Psychometric functions for gap detection of temporal gaps in wideband noise were measured in a "yes/no" paradigm from normal-hearing young and aged subjects with closely matched audiograms. The effects of noise-burst duration, gap location, and uncertainty of gap location were tested. A typical psychometric function obtained in this study featured a steep slope, which was independent of most experimental conditions as well as age. However, gap thresholds were generally improved with increasing duration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
84
2
34

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 45 publications
11
84
2
34
Order By: Relevance
“…8,9 In trying to locate the physiological mechanism of temporal resolution, some authors have suggested that auditory nerve fibers participate significantly in the process. 5,10,11 Other studies, however, have shown that processing is more central. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Temporal resolution depends on the separation of different auditory stimuli; the role of the initial part of the stimulus and the coding precision of this response are crucial.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…8,9 In trying to locate the physiological mechanism of temporal resolution, some authors have suggested that auditory nerve fibers participate significantly in the process. 5,10,11 Other studies, however, have shown that processing is more central. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Temporal resolution depends on the separation of different auditory stimuli; the role of the initial part of the stimulus and the coding precision of this response are crucial.…”
Section: Introductionmentioning
confidence: 90%
“…[1][2][3][4][5][6][7] The auditory ability for temporal resolution is the minimum time required for separating or resolving acoustic events. 8,9 In trying to locate the physiological mechanism of temporal resolution, some authors have suggested that auditory nerve fibers participate significantly in the process.…”
Section: Introductionmentioning
confidence: 99%
“…The shortest gap that a listener can detect (relative to the standard) is called a gap detection threshold (GDT). Psychophysical GDTs are influenced by a number of stimulus factors, including marker bandwidth (Eddins, Hall, & Grose, 1992;Snell, Ison, & Frisina, 1994), marker duration (He, Horwitz, Dubno, & Mills, 1999), monotic, diotic, or dichotic presentation modes (Gordon-Salant & Fitzgibbons, 1999;He, et al, 1999;Lister & Roberts, 2005), and the spectral similarity of the markers before and after the gap (Lister, Besing & Koehnke, 2002;Oxenham, 2000).…”
mentioning
confidence: 99%
“…The shortest gap that a listener can detect (relative to the standard) is called a gap detection threshold (GDT). Psychophysical GDTs are influenced by a number of stimulus factors, including marker bandwidth (Eddins, Hall, & Grose, 1992;Snell, Ison, & Frisina, 1994), marker duration (He, Horwitz, Dubno, & Mills, 1999), monotic, diotic, or dichotic presentation modes (Gordon-Salant & Fitzgibbons, 1999;He, et al, 1999;Lister & Roberts, 2005), and the spectral similarity of the markers before and after the gap (Lister, Besing & Koehnke, 2002;Oxenham, 2000).Behavioral studies have shown that, when the stimuli that mark the silent gap are noise bands of similar frequency, known as within-channel gap detection, the task is relatively easy and GDTs are small (Lister & Roberts, 2005;Lister, et al, 2002). When the noise bands that mark the gap are of different frequencies, known as across-channel gap detection, the task is more difficult and GDTs are larger (Lister & Roberts, 2005;Lister, et al, 2002).…”
mentioning
confidence: 99%
“…However, the HI listeners in this study were on average older than the NH listeners in the study by Wojtczak et al (2012) used as a control group. A large number of studies have reported clear effects of age on gap detection and gap-duration discrimination for both within-channel and across-channel markers (Fitzgibbons and Gordon-Salant 1994;Schneider et al 1994;He et al 1999;Lister et al 2000Lister et al , 2002Lister and Roberts 2005). Since the NH and HI listeners compared in this study were not age-matched, some of the observed differences between their data may reflect poorer coding of temporal information or a reduced ability to integrate temporal information across frequency due to the age of the HI listeners.…”
Section: Age Versus Hearing Lossmentioning
confidence: 74%